Susceptibility of Rickettsia conorii, R. rickettsii, and Coxiella burnetii to PD 127,391, PD 131,628, pefloxacin, ofloxacin, and ciprofloxacin. - Jabarit-Aldighieri, N (1992)
Plaque formation and dye uptake assays were used to measure the MICs of PD 127,391 and PD 131,628 against Rickettsia species. The MICs of PD 127,391 were 0.25 microgram/ml for Rickettsia rickettsii and 0.125 to 0.25 microgram/ml for Rickettsia conorii. The MICs of PD 131,628 were 0.25 to 0.5 microgram/ml for R. rickettsii and 0.5 microgram/ml for R. conorii. As determined by the shell vial technique, 15 strains of Coxiella burnetii were susceptible to PD 127,391 and PD 131,628 (MIC, < or = 1 microgram/ml), while one strain of C. burnetii (MP10) was of intermediate susceptibility.